Correlation between Qualitative Characteristics and Genotype Resistance of Local and Introduced Pepper Varieties Against Anthracnose Disease - Hafsah, Siti; Firdaus, Firdaus (Journal of Tropical Horticulture, 2020)
This study was aimed at obtaining information related to genetic parametric against anthracnose diseases caused by Colletotrichum capsici, which attacked several pepper genotypes. The research was conducted in a net house at the Faculty of Agriculture, Universitas Syiah Kuala, Banda Aceh, from July to December 2017, and it was divided into two experiments: 1) planting the peppers which carried out in a net house. This experiment employed Randomized Block Design (RBD) Non-Factorial and 2) anthracnose resistance assay.Â  This assay applied using Completely Randomized Design (CRD) Non-Factorial with the only factor observed: 11 pepper genotypes (IPBC15, IPBC15D2, IPBC15D3, IPBC15D4, Udeng, Lamando Lapaben, Super Amando, Lanyoe, Lado F1, Kastilo F1, and PM999 F1), with three replications. The results showed that the genotypes IPBC15, IPBC15D2, IPBC15D4, Udeng, Lamando Lapaben, Lado F1 exhibited moderate resistance, while genotypes IPBC15D3, Super Amando, Lanyoe, Kastilo F1 and PM999 F1 were susceptible to the disease. The wide variety of genetic and high heritability was found in stem length, flowering age, length of fruit stalk, fruit length, fruit diameter, and skin thickness, while narrow and moderate genetic variability was found in stem diameter and harvest age. The coefficient of genetic diversity in stem length, length of fruit stalk, and fruit length was found to be moderate and expressed low diversity in stem diameter, flowering age, and skin thickness. Stem diameter and skin thickness also showed a negative correlation to disease severity.